2019
DOI: 10.1016/j.jaci.2018.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Transmaternal Helicobacter pylori exposure reduces allergic airway inflammation in offspring through regulatory T cells

Abstract: We conclude that exposure to H pylori has consequences not only for the carrier but also for subsequent generations that can be exploited for interventional purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 57 publications
1
32
1
1
Order By: Relevance
“…15 Indeed, the same group showed that transmaternal exposure to H pylori extract in utero and/or during lactation induced strong protective effects against allergic airway inflammation in both the first-and, intriguingly, second-generation offspring. 28 Treatment with H pylori VacA mediated a similar protective effect which correlated with the skewing of T-cell responses toward regulatory rather than effector functions, as characterized by the expansion of Treg cell subsets expressing CXC chemokine receptor 3 (Cxcr3) or RORγt, as well as demethylation of the Foxp3 locus. 28 These findings raise interesting questions about the potential of H pylori to protect against allergic asthma and other atopic conditions, warranting investigations in human subjects under controlled laboratory conditions.…”
Section: Downregulation Of Host Immune Responses and Induction Of Tmentioning
confidence: 94%
See 4 more Smart Citations
“…15 Indeed, the same group showed that transmaternal exposure to H pylori extract in utero and/or during lactation induced strong protective effects against allergic airway inflammation in both the first-and, intriguingly, second-generation offspring. 28 Treatment with H pylori VacA mediated a similar protective effect which correlated with the skewing of T-cell responses toward regulatory rather than effector functions, as characterized by the expansion of Treg cell subsets expressing CXC chemokine receptor 3 (Cxcr3) or RORγt, as well as demethylation of the Foxp3 locus. 28 These findings raise interesting questions about the potential of H pylori to protect against allergic asthma and other atopic conditions, warranting investigations in human subjects under controlled laboratory conditions.…”
Section: Downregulation Of Host Immune Responses and Induction Of Tmentioning
confidence: 94%
“…26 Thus, NOD1-driven IL-33 production during chronic H pylori infection may protect against excessive inflammatory responses and favor bacterial persistence. 15,28 Altobelli et al 15 15 The induction of immune tolerance was mediated, at least in part, by VacA. 27 In addition to dampening host inflammatory responses, there is increasing evidence that H pylori induces a form of immune tolerance and, moreover, that this condition may develop very early in life.…”
Section: Downregulation Of Host Immune Responses and Induction Of Tmentioning
confidence: 99%
See 3 more Smart Citations